KAJIAN KONSENTRASI AIR KELAPA MUDA SEBAGAI ORGANIC PRIMING TERHADAP VIABILITAS BENIH KACANG MERAH YANG TERDETERIORASI - Yosefina Lewar; Katarina N. Kumanireng; Ali Hasan (Partner, 2023)
The aim of the study was to determine the viability of kidney bean seed varieties Inerie is organic priming with different concentrations of young coconut water. This research was conducted in the Horticulture laboratory and screen house in the month of October 2021. The research design used was a Randomized Design Complete with 7 concentration treatments which were 4 repeated. The treatment used is the concentration of young coconut water that is 0% (control), 10%, 20%, 30%, 40%, 50%, and 60%. The results showed that a concentration of 30% young coconut water as organic priming can increase seed germination (83.00%) and seed growth speed (22.02%/day), and a concentration of 10% can increase seed growth synchrony (81.00%).Key Words:  Invigoration, Kidney Bean, Organic Priming, Young Coconut Water